Methane Emission Quantification Using UAV-based Measurements - Comparing Existing Landfill Methane Monitoring Methods - Powis,Kajsa-Lisa (Student thesis series INES, 2025)
According to the Intergovernmental Panel on Climate Change (IPCC), atmospheric methane (CH4) concentrations are considered a crucial factor in global warming, particularly in the near term, due to its high warming potential (~ 80 times more potent than carbon dioxide, or CO2) and shorter atmospheric lifetime compared to CO2. CH4 emissions have more than doubled since the industrial revolution and CH4 has increased exponentially from the 1850’s to the current level of 1943 ppb. A substantial contribution stems from landfills and waste constituting 68 Mt per year, or 17% of total anthropogenic CH4 emissions. Furthermore, in Sweden, approximately 13% of all anthropogenic CH₄ emissions are generated from landfills. There is therefore a need to mitigate fugitive CH4 emissions from landfills in the waste sector: both in Sweden and the rest of the world, necessitating accurate and scalable quantification techniques. By utilizing strategies like UAV-based methane measurement techniques, Swedish methane emissions, and particularly the effectiveness of implemented mitigation measures, can be efficiently monitored. Monitoring greenhouse gas emissions is an important contribution to achieving Sweden’s emissions reduction goals. This study evaluates the performance and applicability of the UAV-based GASTRAQ method by comparing its results from field campaigns at Filborna and Rönneholm landfill with those from a recently validated Drone Flux Method (DFM), applied to data from a wastewater sludge landfill in Linköping Sweden. Both methods rely on mass balance theory yet differ in the sense that GASTRAQ utilises ground-based wind profiles while DFM incorporates real-time onboard wind sensing. Flux estimates were analysed alongside uncertainty tests, highlighting that the DFM is more scalable and adaptable due to its wind assumptions, while GASTRAQ is susceptible to inaccuracies under variable wind conditions. Relative errors varied considerably across campaigns, indicating that wind field characterization is a primary uncertainty source. Despite these limitations, GASTRAQ remains practical for routine monitoring in stable atmospheric conditions. The study concludes that UAV-based methods can yield adequate CH4 flux estimates, provided that site-specific constraints such as wind turbulence and spatial coverage are adequately quantified and that the footprint of the flights are representative for the landfill. Future developments including onboard wind sensors and autonomous flight paths may improve flux accuracy and enable broader regulatory application of UAV-based CH₄ monitoring in the waste sector.
Keywords: Methane; CH4; UAV; Mass Balance Theory; GASTRAQ; DFM; Drone Flux Method; Landfill; Rönneholm; Filborna; Linköping